Rotating Disk Electrode Standardization and Best Practices in Acidic Oxygen Evolution for Low-Temperature Electrolysis - Alia, Shaun M.; Danilovic, Nemanja (Frontiers in Energy Research, 2022)
Efforts in oxygen evolution catalyst development have significantly increased, and often use rotating disk electrode half-cells to evaluate intrinsic kinetics and screen materials for short-term durability. Standardiz-ing rotating disk electrode test protocols is critical to experimental accuracy, to realistically assess their po-tential impact at the device-level, and to assess how different catalyst approaches and concepts are priori-tized. The goal of this study is to provide standardized test protocols and suggest best practices to help re-duce variability in ex-situ materials characterization in the broader community. Specifically, these protocols focus on test cleanliness and materials choices, including how electrodes are prepared and tested, and the impact on activity observations.